Diversity Analysis of the Rice False Smut Pathogen Ustilaginoidea virens in Southwest China - Rongtao Fu; Cheng Chen; Jian Wang; Yao Liu; Liyu Zhao; Daihua Lu (Journal of Fungi, 2022)
Rice false smut caused by Ustilaginoidea virens is a destructive disease in rice cropping areas of the world. The present study is focused on the morphology, pathogenicity, mating-type loci distribution, and genetic characterization of different isolates of U. virens. A total of 221 strains of U. virens were collected from 13 rice-growing regions in southwest China. The morphological features of these strains exhibited high diversity, and the pathogenicity of the smut fungus showed significant differentiation. There was no correlation between pathogenicity and sporulation. Mating-type locus (MAT) analysis revealed that all 221 isolates comprised heterothallic and homothallic forms, wherein 204 (92.31%) and 17 (7.69%) isolates belonged to heterothallic and homothallic mating types, respectively. Among 204 strains of heterothallic mating types, 62 (28.05%) contained MAT1-1-1 idiomorphs, and 142 isolates (64.25%) had the MAT1-2-1 idiomorph. Interestingly, strains isolated from the same fungus ball had different mating types. The genetic structure of the isolates was analyzed using simple sequence repeats (SSRs) and single-nucleotide polymorphisms (SNPs). All isolates were clustered into five genetic groups. The values of Nei’s gene diversity (H) and Shannon’s information index (I) indicated that all strains as a group had higher genetic diversity than strains from a single geographical population. The pairwise population fixation index (FST) values also indicated significant genetic differentiation among all compared geographical populations. The analysis of molecular variation (AMOVA) indicated greater genetic variation within individual populations and less genetic variation among populations. The results showed that most of the strains were not clustered according to their geographical origin, showing the rich genetic diversity and the complex and diverse genetic background of U. virens in southwest China. These results should help to better understand the biological and genetic diversity of U. virens in southwest China and provide a theoretical basis for building effective management strategies.